Esteban Garibay and the invention of the Navarre pre-Arista - Moya Mangas, Jesús (Huarte de San Juan. Geografía e Historia, 2021)
Esteban de Garibay’s Compendio Histo-rial continues to keep secrets about its genesis and development, as its author is also secretive about his scholar training, method and messa-ges. This article focuses on the part of the work that deals with Navarre –a historical kingdom already conquered and annexed to the crown of Spain–, and specifically on the book about its origins, as an example of a peculiar way of historicizing, modern in its aim but with medie-val traits of Biblical flavour, a sort of providential history of punishment and salvation. The author, who boasts to reject fable as unworthy of History, does not hesitate to exploit it if it is useful for its ideal construction. So he rejects the tradition of a Pyrenean monarchy starting with Iñigo Arista as its first king, to follow an Aragonese fable forged around San Juan de la Peña, which anticipated that monarchy and the Pyrenean reconquest to make it contemporary of the Asturian one. Ga-ribay of course disowns details of this invention whilst he accepts it in substance, refining it in order to enhance its navarrismo, fixing the pree-minence of Navarre over Aragon in a context of exaltation of the Basque character in Spain.
Keywords: Esteban de Garibay; ancient history of Navarre; Pyrenean reconquest; Aragon and Navarre